Approaches to Gene Mutation Analysis Using Formalin-Fixed Paraffin-Embedded Adrenal Tumor Tissue From Patients With Primary Aldosteronism - Nanba, Kazutaka; Rainey, William E.; Udager, Aaron M. (Frontiers in Endocrinology, 2021)
Aldosterone production is physiologically under the control of circulating potassium and angiotensin II as well as adrenocorticotropic hormone and other secretagogues such as serotonin. The adrenal’s capacity to produce aldosterone relies heavily on the expression of a single enzyme, aldosterone synthase (CYP11B2). This enzyme carries out the final reactions in the synthesis of aldosterone and is expressed almost solely in the adrenal zona glomerulosa. From a disease standpoint, primary aldosteronism (PA) is the most common of all adrenal disorders. PA results from renin-independent adrenal expression of CYP11B2 and production of aldosterone. The major causes of PA are adrenal aldosterone-producing adenomas (APA) and adrenal idiopathic hyperaldosteronism. Our understanding of the genetic causes of APA has significantly improved through comprehensive genetic profiling with next-generation sequencing. Whole-exome sequencing has led to the discovery of mutations in six genes that cause renin-independent aldosterone production and thus PA. To facilitate broad-based prospective and retrospective studies of APA, recent technologic advancements have allowed the determination of tumor mutation status using formalin-fixed paraffin-embedded (FFPE) tissue sections. This approach has the advantages of providing ready access to archival samples and allowing CYP11B2 immunohistochemistry-guided capture of the exact tissue responsible for inappropriate aldosterone synthesis. Herein we review the methods and approaches that facilitate the use of adrenal FFPE material for DNA capture, sequencing, and mutation determination.